2019
DOI: 10.1177/1077546319844092
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and handling stability analysis of articulated vehicle with hydraulically interconnected suspension

Abstract: Anti-roll hydraulically interconnected suspension (HIS) due to its roll-vibration stiffness and damping performance has been studied and applied in passenger vehicles, buses, and tri-axle straight vehicles. However, very few investigations have been made on six-axle articulated vehicles with the HIS system. Moreover, rollover accidents involving articulated vehicles cause severe casualties, which have attracted wide attention in the vehicle safety field. This calls for a design of a new suspension control tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…q p1 and q p2 are the flow rate at the inlet and the schematic of the pipeline is shown in Figure 4. Thus, the pipeline can be modeled as 24,25…”
Section: Sdahis System Modelmentioning
confidence: 99%
“…q p1 and q p2 are the flow rate at the inlet and the schematic of the pipeline is shown in Figure 4. Thus, the pipeline can be modeled as 24,25…”
Section: Sdahis System Modelmentioning
confidence: 99%
“…The result verified that the inerter could effectively reduce the vibration. Li X–P et al applied the inerter to the two-stage vehicle suspension to improve the vibration reduction performance(Li et al, 2019). To suppress the sway vibration of the aircraft landing gear, Li Y et al added the inerter to the sway vibration suppression device and achieved good results (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 22 studied on minig vehicle and tuned the pitch and bounce response through modal analysis and showed that the enhancement of coopereative contol of bounce and pitch motion modes improves the ride and handling. Li et al 23 improved handling of six-axle vehicle with proposed HIS system and showed that the proposed control technique effectively improved the handling performance of articulated vehicle. Qi et al 24 improved the ride of a bus with help of electronic controller and air spring actuator in terms of tire forces and bounce acceleration and handling in terms of lateral acceleration, roll angle, yaw rate and rollover critical factor simultaneously.…”
Section: Introductionmentioning
confidence: 99%